Forward-angle electron spectroscopy in heavy-ion atom collisions studied at the ESR. (July 2015) - Hillenbrand, P-M; Hagmann, S; Banaś, D; Blumenhagen, K-H; Brandau, C; Chen, W; De Filippo, E; Gumberidze, A; Guo, D L; Jakubassa-Amundsen, D H; Lestinsky, M; Litvinov, Yu A; et al.
Synopsis: For the collisions system U 88+ + N2 @ 90 MeV/u the emitted cusp electrons have been studied, and the three processes contributing to the electron cusp were compared to individual theoretical calculations.